PRESCRIPCIONES MÉDICAS DE IBN JATIMA PARA EL TRATAMIENTO PALIATIVO EN LA ENFERMEDAD DE LA PESTE BUBÓNICA - Cambra, Luisa Maria Arvide (European Scientific Journal, ESJ, 2013)
The article is an approach to the study of the treatise of the pest of Ibn Khatima of Almeria (d.circa 1369), one of the most representative doctors of Muslim Spain in the 14th century, and includes some preliminary notes by way of Introduction about the life and the work of the author, with special reference to Tahsil al-garad, the book that Ibn Khatima wrote about this terrible disease, and an appendix with the Spanish translation of folios 75vº-77vº from the Arabic manuscript no. 1785 Library of El Escorial, which collect part of the Question VI of the treatise and that refer to some therapeutic prescriptions to alleviate the ravages of the disease, possessing a high medical and pharmacological value.